Generalized pustular psoriasis in a 92‐year‐old man with a homozygous nonsense mutation in IL36RN. Issue 3 (7th December 2017) - Ueda, Yoshitaka; Komine, Mayumi; Kamiya, Koji; Tsuda, Hidetoshi; Maekawa, Takeo; Murata, Satoru; Ohtsuki, Mamitaro
Abstract: A 92‐year‐old man developed an erythematous eruption on the trunk and extremities with numerous pustules accompanied by fever. He had never experienced pustular eruption or been diagnosed with psoriasis previously. Skin biopsy revealed Kogoj's spongiform pustule, and he was diagnosed with generalized pustular psoriasis (GPP). Genomic DNA was extracted from his peripheral blood and the sequence of IL36RN gene was analyzed, which revealed a p.Arg10X homozygous mutation. Several cases of elderly‐onset GPP have been reported, however, this is the oldest case of GPP. The existence of splice variants of IL36RN was suspected, but we could not detect any splice variants of IL36RN in this case or in a healthy control from peripheral blood samples.